Template-controlled mineralization: Determining film granularity and structure by surface functionality patterns - Blumenstein, Nina J.; Berson, Jonathan; Walheim, Stefan; Atanasova, Petia; Baier, Johannes; Bill, Joachim; Schimmel, Thomas (Beilstein Journal of Nanotechnology, 2015)
We present a promising first example towards controlling the properties of a self-assembling mineral film by means of the functionality and polarity of a substrate template. In the presented case, a zinc oxide film is deposited by chemical bath deposition on a nearly topography-free template structure composed of a pattern of two self-assembled monolayers with different chemical functionality. We demonstrate the template-modulated morphological properties of the growing film, as the surface functionality dictates the granularity of the growing film. This, in turn, is a key property influencing other film properties such as conductivity, piezoelectric activity and the mechanical properties. A very pronounced contrast is observed between areas with an underlying fluorinated, low energy template surface, showing a much more (almost two orders of magnitude) coarse-grained film with a typical agglomerate size of around 75 nm. In contrast, amino-functionalized surface areas induce the growth of a very smooth, fine-grained surface with a roughness of around 1 nm. The observed influence of the template on the resulting clear contrast in morphology of the growing film could be explained by a contrast in surface adhesion energies and surface diffusion rates of the nanoparticles, which nucleate in solution and subsequently deposit on the functionalized substrate.
Keywords: bioinspired synthesis; polymer-blend lithography; surface functionality; template-controlled self-assembly; zinc oxide thin film

(untitled) - Liu, B.; Cao, Y.; Huang, Z.; Duan, Y.; Che, S. (Adv. Mater., 2015)

(untitled) - Ryu, J.; Kim, S.; Kim, H. I.; Jo, E.-H.; Kim, Y. K.; Kim, M.; Jang, H. D. (Chem. Eng. J., 2015)

(untitled) - Pitta Bauermann, L.; Gerstel, P.; Bill, J.; Walheim, S.; Huang, C.; Pfeifer, J.; Schimmel, T. (Langmuir, 2010)

(untitled) - Coltrin, M. E.; Hsu, J. W. P.; Scrymgeour, D. A.; Creighton, J. R.; Simmons, N. C.; Matzke, C. M. (J. Cryst. Growth, 2008)

(untitled) - Hsu, J. W. P.; Clift, W. M.; Brewer, L. N. (Langmuir, 2008)

(untitled) - Collins, R. J.; Shin, H.; DeGuire, M. R.; Heuer, A. H.; Sukenik, C. N. (Appl. Phys. Lett., 1996)

(untitled) - Schmahl, W. W.; Griesshaber, E.; Kelm, K.; Ball, A.; Goetz, A.; Xu, D.; Kreitmeier, L.; Jordan, G. (Z. Kristallogr., 2012)

(untitled) - Kellermeier, M.; Cölfen, H.; García-Ruiz, J. M. (Eur. J. Inorg. Chem., 2012)

(untitled) - Ma, J.; Wang, J.; Ai, X.; Zhang, S. (Biotechnol. Adv., 2014)

(untitled) - Checa, A. G.; Rodrı́guez-Navarro, A. B. (Biomaterials, 2005)

(untitled) - Petrack, J.; Jost, S.; Boenigk, J.; Epple, M. (Beilstein J. Nanotechnol., 2014)

(untitled) - Pohl, A.; Weiss, I. M. (Beilstein J. Nanotechnol., 2014)

(untitled) - Eisele, R.; Blumenstein, N. J.; Baier, J.; Walheim, S.; Schimmel, T.; Bill, J. (CrystEngComm, 2014)

(untitled) - Detsri, E.; Popanyasak, J. (Colloids Surf., A, 2015)

(untitled) - Kadiri, H.; Kostcheev, S.; Turover, D.; Salas-Montiel, R.; Nomenyo, K.; Gokarna, A.; Lerondel, G. (Beilstein J. Nanotechnol., 2014)

(untitled) - Rensmo, H.; Keis, K.; Lindström, H.; Södergren, S.; Solbrand, A.; Hagfeldt, A.; Lindquist, S.-E.; Wang, L. N.; Muhammed, M. (J. Phys. Chem. B, 1997)

(untitled) - Arya, S. K.; Saha, S.; Ramirez-Vick, J. E.; Gupta, V.; Bhansali, S.; Singh, S. P. (Anal. Chim. Acta, 2012)

(untitled) - Ozgur, U.; Hofstetter, D.; Morkoc, H. (Proc. IEEE, 2010)

(untitled) - Assaud, L.; Monyoncho, E.; Pitzschel, K.; Allagui, A.; Petit, M.; Hanbücken, M.; Baranova, E. A.; Santinacci, L. (Beilstein J. Nanotechnol., 2014)

(untitled) - Ismail, B.; Abaab, M.; Rezig, B. (Thin Solid Films, 2001)

(untitled) - Inamdar, A. I.; Mujawar, S. H.; Ganesan, V.; Patil, P. S. (Nanotechnology, 2008)

(untitled) - Gardeniers, J. G. E.; Rittersma, Z. M.; Burger, G. J. (J. Appl. Phys., 1998)

(untitled) - Wang, Z. L. (J. Phys.: Condens. Matter, 2004)

(untitled) - Yang, P.; Yan, H.; Mao, S.; Russo, R.; Johnson, J.; Saykally, R.; Morris, N.; Pham, J.; He, R.; Choi, H.-J. (Adv. Funct. Mater., 2002)

(untitled) - AlZayed, N. S.; Ebothé, J.; Michel, J.; Kityk, I. V.; Yanchuk, O. M.; Prots, D. I.; Marchuk, O. V. (Physica E, 2014)

(untitled) - Gerstel, P.; Hoffmann, R. C.; Lipowsky, P.; Jeurgens, L. P. H.; Bill, J.; Aldinger, F. (Chem. Mater., 2006)

(untitled) - Gerstel, P.; Lipowsky, P.; Durupthy, O.; Hoffmann, R. C.; Bellina, P.; Bill, J.; Aldinger, F. (J. Ceram. Soc. Jpn., 2006)

(untitled) - Lin, W.-C.; Lee, S.-H.; Karakachian, M.; Yu, B.-Y.; Chen, Y.-Y.; Lin, Y.-C.; Kuob, C.-H.; Shyue, J.-J. (Phys. Chem. Chem. Phys., 2009)

(untitled) - Shyue, J.-J.; De Guire, M. R.; Nakanishi, T.; Masuda, Y.; Koumoto, K.; Sukenik, C. N. (Langmuir, 2004)

(untitled) - Cuvillier, N.; Rondelez, F. (Thin Solid Films, 1998)

(untitled) - Janssen, D.; De Palma, R.; Verlaak, S.; Heremans, P.; Dehaen, W. (Thin Solid Films, 2006)

(untitled) - Huang, C.; Moosmann, M.; Jin, J. H.; Heiler, T.; Walheim, S.; Schimmel, T. (Beilstein J. Nanotechnol., 2012)